Lentinula edodes biotechnology : from Lentinan to lectins - Nikitina, Valentina E. (Array, 2007)
Lentinula edodes was the first medicinal macrofungus to enter the realm of modern biotechnology. The present paper briefly reviews the history of the modern biotechnology of this mushroom starting with the production of the polysaccharide preparation lentinan, and ending with an overview of our own work regarding the production of lectins. Our work with lectins has involved studies of the effect of initial pH, carbon and nitrogen sources and the C:N ratio on lectin production in both the mycelium and culture medium. We have shown that lectin activity is related to morphological development, with the activity being highest in extracts of the pigmented mycelial films that precede fruiting body production